2023
DOI: 10.1049/htl2.12052
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health records perception among three healthcare providers specialties in Saudi Arabia: A cross‐sectional study

A. Karim Jabali,
Fuad A. Abdulla

Abstract: Worldwide, more health care facilities are adapting the use of electronic health record (EHR). Healthcare providers (HCP) have different perceptions toward the use of EHR. To investigate the perception of three classes of HCP in Saudi Arabia toward using EHR, a questionnaire (targeting satisfaction, easiness, and benefits of use as major perception indicators) was prepared. The questionnaire was assessed by an expert panel for content validity. The questionnaire internal consistency was examined using Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Some respondents considered EMR detrimental in this regard. 16 This may indicate the need for improvement in the ability of EMR to detect and prevent medication-related medical errors. Respondents generally expressed satisfaction with the use of EMR, especially in terms of system user-friendliness and as an alternative to paper-based recording.…”
Section: Discussionmentioning
confidence: 99%
“…Some respondents considered EMR detrimental in this regard. 16 This may indicate the need for improvement in the ability of EMR to detect and prevent medication-related medical errors. Respondents generally expressed satisfaction with the use of EMR, especially in terms of system user-friendliness and as an alternative to paper-based recording.…”
Section: Discussionmentioning
confidence: 99%
“…Saudi Arabia has made progress in implementing e-health in a range of care contexts, such as hospitals, laboratories and prescription services [ 6 ]. Prior research has examined the rate of uptake of these technologies, for instance using the Healthcare Information and Management Systems Society (HIMSS) adoption model with some care centres achieving a stage 7 accreditation, the highest stage possible [ 1 , 7 ]. EHR technologies used within KSA are sourced from a variety of developers, including Epic and Cerner, as well as other high-rated producers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, a significant body of research has examined stakeholders’ awareness of these EHR systems and begun to identify factors that influence their successful implementation, including the requirement for comprehensive training, and efficient and effective leadership in transitioning to these new systems [ 6 , 7 ]. Several research works have also identified dissatisfaction among physicians and nurses as a key factor affecting EHR adoption [ 8 , 9 ], which can be caused by financial issues; complexity of systems, including multiplicity of screens, options and navigational aids; and a lack of customizability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations